1968
DOI: 10.1104/pp.43.7.1141
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Auxin Protectors. V. On the Mechanism of IAA Protection by Protector-I of the Japanese Morning Glory

Abstract: Abstract. The mechanism of auxin protection by auxin protector-I (Pr-I) of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1969
1969
1995
1995

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Thus auxin protection is greatest in leaves and interriodes elongating most rapidly, and diminishes as the tissue matures (29,30). Similar substances have been identified in other plants such as tobacco (15,16), cocklebur, Kalanchoe, Nicotiana affinis, N. glauca, N. ri'stica, sunflower, and tomato (24, and (25).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Thus auxin protection is greatest in leaves and interriodes elongating most rapidly, and diminishes as the tissue matures (29,30). Similar substances have been identified in other plants such as tobacco (15,16), cocklebur, Kalanchoe, Nicotiana affinis, N. glauca, N. ri'stica, sunflower, and tomato (24, and (25).…”
mentioning
confidence: 73%
“…The association of high levels of auxin protectors with the juvenile state will be reported elsewhere, as will a more detailed discussion of why these substances are probably causally related to the juvenile state. Suffice it to point out here that protector-I of the Japanese morning glory exerts its protecting activity by acting as an antioxidant which interferes with the peroxidase-catalyzed oxidation of IAA (22,25). Preliminary experiments have indicated that this is also true of protectors A anid II, and that all 3 protectors may act as poisers, stabilizing the redox state of chemical systems, not merely the oxidation of IAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both indole-3-acetic acid and ferulic acid are substrates of horseradish peroxidase in the presence of H202, and indole-3-acetic acid competitively inhibits the oxidation of ferulic acid. A model for the enzymatic oxidation of indole-3-acetic acid catalyzed by peroxidase is proposed.It is well established that plants contain enzymes (5,11,15,(18)(19)(20)21). Most inhibitors are of low molecular weight, although Stonier et al (18,20) reported phenolic inhibitors from Pharbitis with molecular weights of 5,000 to 10,000, based upon behavior on sephadex gels.…”
mentioning
confidence: 99%
“…Most inhibitors are of low molecular weight, although Stonier et al (18,20) reported phenolic inhibitors from Pharbitis with molecular weights of 5,000 to 10,000, based upon behavior on sephadex gels. The association of high inhibitor concentrations with actively growing tissues suggests that inhibitors promote growth by preventing IAA destruction by endogenous IAA oxidase-the "auxin protector" concept of Stonier and Yoneda (20).Several workers have sought to clarify the mechanism(s) by which phenolic inhibitors delay the peroxidase-catalyzed oxidation of IAA (15,(18)(19)(20)21 Gordon and Weber (6). Two ml of test solution were mixed with 4 ml of reagent, and absorbance was measured at 525 nm on a Coleman 46 spectrophotometer equipped with a Gilson transferator.…”
mentioning
confidence: 99%